This changes everything [compact disc, unabridged] : capitalism vs. the climate - Klein, Naomi, 1970- (Simon & Schuster Audio, 2014)
Despite mounting scientific evidence, climate change denial is surging in many wealthy countries, and fossil-fuel extraction has gathered pace. Naomi Klein exposes the work of ideologues who know the difficulties this poses to the free market, and challenges the failing strategies of environmental groups.